Overexpression of Interferon-Inducible Protein 16 Promotes Progression of Human Pancreatic Adenocarcinoma Through Interleukin-1β-Induced Tumor-Associated Macrophage Infiltration in the Tumor Microenvironment - Chen, Jing-Xian; Cheng, Chien-Shan; Gao, Hong-Fang; Chen, Zi-Jie; Lv, Ling-Ling; Xu, Jia-Yue; Shen, Xiao-Heng; Xie, Jing; Zheng, Lan (Frontiers in Cell and Developmental Biology, 2021)
Activation of inflammasomes has been reported in human pancreatic adenocarcinoma (PAAD); however, the expression pattern and functional role of inflammasome-related proteins in PAAD have yet to be identified. In this study, we systemically examined the expression and role of different inflammasome proteins by retrieving human expression data. Several genes were found to be differentially expressed; however, only interferon-inducible protein 16 (IFI16) expression was found to be adversely correlated with the overall survival of PAAD patients. Overexpression of IFI16 significantly promoted tumour growth, increased tumour size and weight in the experimental PAAD model of mice, and specifically increased the population of tumour-associated macrophages (TAMs) in the tumour microenvironment. Depletion of TAMs by injection of liposome clodronate attenuated the IFI16 overexpression-induced tumour growth in PAAD. In vitro treatment of conditioned medium from IFI16-overexpressing PAAD cells induced maturation, proliferation, and migration of bone marrow-derived monocytes, suggesting that IFI16 overexpression resulted in cytokine secretion that favoured TAM population. Further analysis suggested that IFI16 overexpression activated inflammasomes, thereby increasing the release of IL-1β. Neutralization of IL-1β attenuated TAM maturation, proliferation, and migration induced by the conditioned medium from IFI16-overexpressing PAAD cells. Additionally, knockdown of IFI16 could significantly potentiate gemcitabine treatment in PAAD, which may be associated with the reduced infiltration of TAMs in the tumour microenvironment. The findings of our study shed light on the role of IFI16 as a potential therapeutic target for PAAD.